Análisis de los enfoques de desarrollo Móviles Hibridas Xamarin y React Native, en función al aspecto de seguridad para los usuarios, en plataformas Android. - Morante Pisco, Cesar Samuel (2024)
The case study took an in-depth look at hybrid mobile development approaches using Xamarin and React Native, with a critical focus on security for users on Android devices. Through the evaluation of security practices, vulnerability and resistance tests, as well as the comparison of specific features, distinctive aspects that influence the security of applications developed on both platforms were revealed.